(3HZjI GdeQGeihZGjI GdeQGei (B( (3aj GdQei HGdbhS hGdfTGH hGdHfObjI (B)s - (3YdGA GdOjf WjHZG GdCTQai GdHcdeTi GdjhfGfis; (3WjHhZG GdCTQaj , WjHhZG GdGTQaj GdHWdeTj GdjhfGfj, YdGA GdOjf,J (B770 (3g` s
(3ChdgG (B:s
(3jGef jQhe UfYg GdQeGjI hjMce GdCUhd hGdeYGfi Chd GdTQM(B: (3GdMeO ddg GdYGOd MceI GdTGed YdegCeG HYO , aEf Gddg JYGdi MjK aQV YdjfG GdfTGH s
(3GfXQ Qbe (B30 (3ef gPG GdagQS HYfhGf (B" (3ZfjI GdWdGH (B"s
(3HChdgG hBNQgG JOdjSs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B46s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs